Análise de um sistema de reabilitação para membros superiores utilizando ambiente de realidade virtual baseado em Kinect e sEMG - Cardoso, Vivianne Flavia (2016)
Impaired motor function appears as one of the most common symptoms stroke. When the upper limbs are affected, carrying out daily activities is compromised. The recent developments in the field of rehabilitation are exercises in virtual reality environment (RV). Another method used for rehabilitation of the upper limbs of patients after stroke is the EMG biofeedback. Through this biofeedback, the myoelectric signals from the muscle are converted into visual and audio information that allows the patient to control and regulate muscle activity. The objective of this work is to design and evaluate a new form of rehabilitation by biofeedback using RV and surface electromyography (sEMG) to complement conventional therapy upper limb post-stroke patients. The system was developed in accordance with the requirements in the design phase and design, considering the patient's functional limitations, residual skills, a motivating environment and ease of use. He is able to provide feedback of sEMG, the result (through the score in the game) and the angle described. The three games developed, aims to motivate the patient to perform elbow extension movements and meet the principles of motor learning. To develop and evaluate the system experiments were conducted with individuals without motor or neurological involvement. Analyzing the graph obtained by the myoelectric signal filtered and rectified is possible to observe a co-contraction of Bícpes Brachial (BB) and Trícpes Brachial (TB). When we analyze the results of feedback, the data show that and were not found significas differences (p = 0.9216) when playing with the dominant arm (BD) versus non-dominant (BND). However a significant difference is observed when comparing both arms versus BD (BD / BND) and p = 0.0003 vs. BND BD / BND, p = 0.0018. The results of the evaluations through the System Usability Scale (SUS), in the experiments of stage 2 (E2) was ± 81.4; SD ± 3.4 and stage 3 for participants (E3 / P) ± 82.5; SD ± 14.3 and rehabilitation professionals (E3 / PR) ± 81.1; SD ± 7.4). In Goal Attainment Scale (GAS), E2 was ± 73.3; SD ± 2.7; E3 / P ± 72.2; SD ± 6.1 and E3 / PR ± 73.5; SD ± 2.7. The results show good acceptance of the system by the users, and that the objectives expected during the use of the system have been achieved.